Embarazo prolongado en paciente de 24 años - Molina Bajaña, Angela Maria (2018)
Prolonged pregnancy also known as post-term, is that pregnancy that has been extended until 42 weeks of gestation or more than 294 days from the first day of the last menstruation. It is considered as one of the clinical complications that affect both the maternal and fetal health status, in the pregnant woman it can present predisposing factors: Like emotional stress, physical trauma, antecedents of previous prolonged pregnancies, in the fetal ones: macrostomia fetal, hydrocephalus. The diagnosis of prolonged pregnancy is made through a good clinical history, with the correct date of gestational age, with the evaluation of the uterine height, and it is confirmed with the ultrasound of the first trimester. Some women have regular menstrual cycles, but the day of ovulation has many variants a few weeks more or less. As the clutch grows there are children who may have growth restriction and others with extra weight. This makes it difficult to get gestational age. On the other hand, with the ultrasound of the first trimester, it gives us an error rate of 2 to 3 days, which is why this last test is more reliable, to avoid risks of maternal-fetal morbidity and mortality. The treatment will depend on the accuracy of the diagnosis. As long as the maternal and fetal conditions permit, the induction of labor will be sought. The objective of this review is to emphasize the clinical importance of this condition in pregnant women, including timely diagnosis, as well as adequate obstetric management, aimed at avoiding complications that may occur